2010
DOI: 10.1111/j.1464-5491.2010.02972.x
|View full text |Cite
|
Sign up to set email alerts
|

Disparity in management of diabetes and coronary heart disease risk factors by sex in DCCT/EDIC

Abstract: In Type 1 diabetes, women report lower frequency than men in the use of interventions that decrease CHD risk. These findings are consistent with reports in the Type 2 diabetic population, showing that risk-reducing measures are underused in women with diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 24 publications
2
26
1
1
Order By: Relevance
“…[28][29][30][31] Somewhat counterintuitively, males had less use of statins, a finding at variance with the general population. 32,33 The rate of statin use we found, at 34.2 %, is broadly comparable to that found previous studies 18,34,35 ), and recent work utilizing Medicare Part D (at 44 %), 36 but is much higher than in older studies using data from the late 1990's when rates ranged from about 9-17 %, 15,[37][38][39][40] albeit at 16.6 % in U.S. patients. These rate variations likely reflect temporal trends in statin prescribing which reflect trends in the general population.…”
Section: Discussionsupporting
confidence: 85%
“…[28][29][30][31] Somewhat counterintuitively, males had less use of statins, a finding at variance with the general population. 32,33 The rate of statin use we found, at 34.2 %, is broadly comparable to that found previous studies 18,34,35 ), and recent work utilizing Medicare Part D (at 44 %), 36 but is much higher than in older studies using data from the late 1990's when rates ranged from about 9-17 %, 15,[37][38][39][40] albeit at 16.6 % in U.S. patients. These rate variations likely reflect temporal trends in statin prescribing which reflect trends in the general population.…”
Section: Discussionsupporting
confidence: 85%
“…This effect of liraglutide is important because 40-50% of patients with type 1 diabetes in the US concomitantly have the metabolic syndrome (17). At 12 years of follow-up, 30% of patients with type 1 diabetes in Diabetes Control and Complications Trial/Epidemiology of Diabetes Interventions and Complications Trial were obese (18). A similar high proportion of children (30%) with type 1 diabetes are either overweight or obese (19).…”
Section: Discussionmentioning
confidence: 99%
“…Practice guidelines from the American Diabetes Association (ADA) and the American Heart Association (AHA) emphasize similar treatment targets for men and women except during pregnancy (American Diabetes Association, 2013; Mosca et al, 2011). Despite these recommendations, previous studies have indicated that women with diabetes are less likely than men with diabetes to achieve some cardiovascular risk factor targets (Bertoni et al, 2008; Bird et al, 2007; Casagrande, Fradkin, Saydah, Rust, & Cowie, 2013; Chou et al, 2007; Ferrara et al, 2008; Larkin et al, 2010; Tseng et al, 2006; Wexler, Grant, Meigs, Nathan, & Cagliero, 2005; Winston, Barr, Carrasquillo, Bertoni, & Shea, 2009). These studies have primarily been cross-sectional and studied individuals with prevalent diabetes, and so were unable to examine changes in risk factor control and management over time and were not able to study the crucial period immediately after diabetes diagnosis.…”
Section: Introductionmentioning
confidence: 99%